Konstribusi Budaya Organisasi, Komunikasi Organisasi, Kompetensi Kerja, dan Komitmen Kerja Terhadap Kinerja Pegawai di Lingkungan Undiksha - I.P. Parwata; I.G.A. Purnamawati; B.R. Werang (Pascasarjana Universitas Pendidikan Ganesha, 2023)
This study aims to 1) analyze the contribution of organizational culture to employee performance in Undiksha, 2) analyze the contribution of organizational communication to employee performance in Undiksha, 3) analyze the contribution of work competence to employee performance in Undiksha, 4) analyze the contribution of work commitment to employee performance in the Undiksha environment, 5) analyzing the contribution of organizational culture, organizational communication of work competence, and work commitment simultaneously to the performance of employees in the Undiksha environment. This research is an ex-post-facto research. The population in this study were all State Civil Administration Employees (ASN) at Undiksha, totaling 236 employees. The sample of this research was 148 people determined using the Solvin formula with a margin of error of 5%. The designation of the sample was determined by simple random sampling technique. Data collection using a questionnaire and data analysis was carried out using simple regression techniques, multiple regression, and partial correlation with the help of the SPSS application. The results of the study show that: 1) there is a significant contribution of organizational culture to employee performance in the Undiksha environment of 24.1%, 2) there is a significant contribution of organizational communication to employee performance in the Undiksha environment of 24.8%, 3) there is a significant contribution significant contribution of work competence to employee performance in the Undiksha environment of 37.2%, 4) there is a significant contribution of work commitment to employee performance in the Undiksha environment of 32.8%, and 5) simultaneously, there is a significant contribution to organizational culture, communication organization, work competence, and work commitment to employee performance in the Undiksha environment by 51%. Keywords : organizational culture, communication, competence, commitment, performance